Life Cycle of the Cardiac Voltage-Gated Sodium Channel NaV1.5 - Dong, Caijuan; Wang, Ya; Ma, Aiqun; Wang, Tingzhong (Frontiers in Physiology, 2020)
Cardiac voltage-gated sodium channel NaV1.5 encoded by SCN5A is crucial for the upstroke of action potential and excitation of cardiomyocytes. NaV1.5 undergoes complex procedures before it reaches the targeted membrane microdomains and functions normally. The balance among transcription of SCN5A and mRNA decay, endoplasmic reticulum retention and export, Golgi retention and export, selective anchoring and degradation, activation and inactivation of sodium current, is achieved by a variety of protein partners. Subtle alterations can impair NaV1.5 either in expression or in function, finally lead to NaV1.5-associated diseases, like lethal arrythmias and cardiomyopathy.